1982
DOI: 10.1093/jn/112.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Maternal Diet, Serotonin Metabolism at Weaning, and Protein Selection of Progeny

Abstract: Brain serotonin (5HT) metabolism in rats at weaning was examined in relation to their maternal dietary protein (PC) and tryptophan (TRP) concentration and to their protein feeding behavior. Pup brain TRP, 5HT, and 5-hydroxyindoleaceticacid (5HIAA) concentration was unaffected by maternal diet PC (10, 20, or 40%) but was increased by TRP additions (0.66 or 1.86%) to 40% casein diets. Turnover of brain 5HT, measured at weaning after probenecid injection, was inversely related to maternal diet PC (r = .54, P less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Furthermore, many BAPs have been identified in casein and soy protein, and these BAPs are known to affect release of peptide hormones in the GI tract (11,29,30,42) and to be absorbed and present in blood (38). The digestion kinetics of proteins also influence their metabolic activities (3) and brain amino acid concentrations and neural activity (24). Furthermore, increased homocysteine concentrations have been observed at weaning in offspring of S diet-fed dams (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many BAPs have been identified in casein and soy protein, and these BAPs are known to affect release of peptide hormones in the GI tract (11,29,30,42) and to be absorbed and present in blood (38). The digestion kinetics of proteins also influence their metabolic activities (3) and brain amino acid concentrations and neural activity (24). Furthermore, increased homocysteine concentrations have been observed at weaning in offspring of S diet-fed dams (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly the latter is explained by exposure of the pups to the diet, as rats start to eat a solid diet by postnatal day 15 (22). Previous studies have shown that the protein composition of diets fed to rats at postnatal day 17 affects food selection behavior (24).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of digestion of the proteins and the resulting hormonal responses in the dams and peak amino acid concentrations in the fetus may also influence the development of regulatory systems. The digestion and absorption kinetics of dietary proteins influence catabolic and anabolic activities at the whole-body level [ 158 ] and in the liver [ 159 ] and brain amino acid concentrations and neural activity [ 160 , 161 ]. Based on their rate of digestion and absorption, proteins can be classified as either “fast” or “slow” proteins [ 159 , 161 ].…”
Section: Proposed Mechanisms Of Fetal Programming By Proteinsmentioning
confidence: 99%
“…Proteins exhibit their functions in a source-dependent manner. Characteristics of proteins including amino acid composition, (11)(12)(13)(14)(15)(16)(17) amino acid sequence, and bioactive peptides (BAPs) (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) encrypted in protein structures and their digestion kinetics (31)(32)(33)(34)(35) are determinant factors in their effects.…”
Section: Introductionmentioning
confidence: 99%